2017
DOI: 10.1002/cssc.201700389
|View full text |Cite
|
Sign up to set email alerts
|

Designing Highly Efficient CuI Photosensitizers for Photocatalytic H2 Evolution from Water

Abstract: A series of Cu photosensitizers was synthesized, characterized, and investigated for photocatalytic H evolution from water. A structure-property correlation was established for their catalytic activity and photophysical properties, which was further elaborated by DFT calculations. A new Cu photosensitizer (Cu-TPAPhen) with triphenylamine-substituted phenanthroline ligands showed unprecedentedly high turnover numbers of 19 000 when tested in combination with triethylamine as a sacrificial reagent and colloidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 24 publications
(36 reference statements)
6
47
0
Order By: Relevance
“…Starting with the pioneering work by McMillin et al. a rising number of (heteroleptic) copper photosensitizers (CuPS) were developed and successfully applied in intermolecular systems for the photocatalytic production of hydrogen from water …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the pioneering work by McMillin et al. a rising number of (heteroleptic) copper photosensitizers (CuPS) were developed and successfully applied in intermolecular systems for the photocatalytic production of hydrogen from water …”
Section: Figurementioning
confidence: 99%
“…As a consequence of this large distortion the triplet excited states can be efficiently quenched by solvent molecules . A reduced distortion and a shielding through the diphosphine ligand was found for [(DPEphos)Cu(dmp)] + (DPEphos=bis[2‐(diphenylphosphino)phenyl] ether) with a change from 82.5° (S 0 ) to 69.0° (S 1 ) and 70.2° (T 1 ), resulting in a considerably evolution of H 2 . In contrast, the angles between the planes of 1 and 2 in the excited states were obtained by TDDFT calculation to be 60.6° (59.6° in T 1 ) and 50.9° (55.4° in T 1 ), respectively (see Table SI7 and Figure SI 17).…”
Section: Figurementioning
confidence: 99%
“…However, in spite of emerging design principles and active synthetic efforts in developing advanced heteroleptic copper‐based photosensitizers, there is an urgent need to correlate their performance and stability to the underlying geometric structures for rational developments in the future. Although the photophysical and structural properties of these heteroleptic copper photosensitizers have been studied by different techniques such as optical transient absorption, UV/Vis, resonance Raman, electrochemistry, single‐crystal X‐ray diffraction, mass spectrometry, NMR, and EPR spectroscopy, the geometrical reorganization of the triplet excited state has not yet been experimentally demonstrated. Elucidation of the nature of the excited state through direct experimental proof is, however, crucial.…”
Section: Introductionmentioning
confidence: 99%
“…30,45,[49][50][51][52][53][54][55] Recent studies have shown that Cu(I) complexes containing one diimine ligand, and one diphosphine ligand such as 4,5-bis(diphenylphosphino)-9,9dimethyl-xanthine (xantphos), which has a large bite angle and high steric hindrance, can have even longer excited state lifetimes (ns-ms). [56][57][58][59][60] Cu(I) complexes are being increasingly used as photosensitisers in photocatalysis, 24,25,30,51,[61][62][63][64][65][66][67][68][69][70][71][72][73] and dyes-sensitised solar cells. 74 They are also used as antitumor [75][76][77][78] and antibacterial agents [79][80][81][82][83][84][85] due to their innate dark toxicity.…”
Section: Introductionmentioning
confidence: 99%